Cross-Cultural Ties between Ghana and Egypt: The Agency of the Egyptian Community in Accra, Ghana - Agyeman, Edmond Akwasi; Amoako-Gyampah, Akwasi Kwarteng (African Human Mobility Review, 2021)
Ghana is recognized as an important destination of international migrants. In spite of the socio-economic and political upheavals that the country experienced during the early post-independence era leading to the (forced) return of several of its migrant groups, some have still remained and formed permanent communities and integrated into the Ghanaian society. This paper focuses on the Egyptian diaspora in Ghana. It examines: (1) the type of cross-border and transnational ties that Egyptian migrants in Ghana have established between Ghana and Egypt; (2) how these ties generate cross-cultural relations between Ghana and Egypt; and (3) the extent to which these ties provide a privileged economic and political position to the Egyptian community in Ghana. The work is based on the socio-cultural transnationalism theory. A socio-historical method was adopted for the research and apart from the analysis of historical data, eight key informants were interviewed. The paper shows that due to high-profile intermarriages between Ghanaians and Egyptians, coupled with the ‘Nkrumah factor’, the Egyptian community in Ghana occupies a privileged economic and political position in Ghana.